2011
DOI: 10.1097/ncc.0b013e3181f70f83
|View full text |Cite
|
Sign up to set email alerts
|

Between Youth and Adulthood

Abstract: Cervical cancer screening programs are challenged to adapt both information and organizations to new cohorts of women with different needs and life situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
(20 reference statements)
1
5
0
1
Order By: Relevance
“…The category of risk perception included the impact of age on risk perception, women’s views of preventive efforts, and knowledge about cervical cancer and screening. In our study, this category was found to be an important motivator to attend cervical screening, as has been shown in previous research [ 37 , 38 ]. It has previously been reported that older Norwegian women in Norway perceive themselves to be at low risk of sexually transmitted cervical infections, and thus delay their attendance at screening [ 39 ], which is consistent with the reasoning of our Norwegian participants.…”
Section: Discussionsupporting
confidence: 86%
“…The category of risk perception included the impact of age on risk perception, women’s views of preventive efforts, and knowledge about cervical cancer and screening. In our study, this category was found to be an important motivator to attend cervical screening, as has been shown in previous research [ 37 , 38 ]. It has previously been reported that older Norwegian women in Norway perceive themselves to be at low risk of sexually transmitted cervical infections, and thus delay their attendance at screening [ 39 ], which is consistent with the reasoning of our Norwegian participants.…”
Section: Discussionsupporting
confidence: 86%
“…Each participant's contribution was highlighted in a separate colour (Blomberg, Widmark, Temestedt, Törnberg, & Tishelman, 2011). In this way, it was easy to follow the different opinions of each participant in the interview.…”
Section: Recruitment and Data Collectionmentioning
confidence: 99%
“…Net 31 proc. toriais, atlikusi kokybinį tyrimą, nustatė, jog trisdešimtmetės moterys labiau rūpinasi savo reprodukcine sveikata, pastojimu ir gimdymu, o ne vėžio prevencija, kuri, jų nuomone, jauname amžiuje neaktuali [24]. [25].…”
Section: Rezultatų Aptarimasunclassified